Profiling Solute Carrier Transporters in the Human Blood–Brain Barrier. Issue 6 (5th September 2013) - Geier, E G; Chen, E C; Webb, A; Papp, A C; Yee, S W; Sadee, W; Giacomini, K M
<x xml:space="preserve">Abstract</x> The neuroprotective function of the blood–brain barrier (BBB) presents a major challenge for drug delivery to the central nervous system (CNS). Critical to this function, BBB membrane transporters include the ATP‐binding cassette (ABC) transporters, which limit drug penetration across the BBB, and the less‐well‐studied solute carrier (SLC) transporters. In this work, expression profiling of 359 SLC transporters, comparative expression analysis with kidney and liver, and immunoassays in brain microvessels (BMVs) identified previously unknown transporters at the human BBB. Clinical Pharmacology & Therapeutics (2013); 94 6, 636–639. doi:10.1038/clpt.2013.175